Are We Educating, Our Children, About Hygiene? Are We Talking, With Them, About It? Perineal Hygiene Education - Gupta, Deepak (Indian Journal of Community Health, 2018)
Cancer screening has always focused on screening lone individuals even when sexually transmitted diseases (STDs) have been traditionally known to require concurrent treatment of all current sexual partners. This shared responsibility towards the sexual partners cannot be limited only to the prevention and treatment of STDs, especially when human papillomavirus (HPV), which is a STD, has been implicated in the etio-pathogenesis of cervical, penile and anal cancers besides other perineal cancers. Consequently, educating Indian population about our personal perineal hygienic practices is of utmost importance to help curtailing the non-“contagious” spread of cancers.